การประเมินความสัมพันธ์ทางพันธุกรรมและการจำแนกบัวสายและลูกผสมด้วยเครื่องหมายสก๊อต - สุขสกุล สุรกฤษฏิ์; ธนานันต์ ธีระชัย; ธนานันต์ นฤมล (Thai Journal of Science and Technology, 2018)
Abstract Currently, Nymphaea is widely used as ornamental flowers and for breeding, therefore the classification by morphology is difficult and confusing. This research, the relationships among 25 Nymphaea sp. and their hybrids from Pangubol Suan Bua in Nonthaburi province were investigated using start codon targeted (SCoT) technique. In the total of 80 primers used, 17 primers, which gave obvious amplified PCR products, were selected. Then, the selected primers were used for polymerase chain reaction (PCR) and resulted in 224 DNA bands ranging from 300 to 2,500 bp. The number of polymorphic bands was 220 (98.21 %). A dendrogram was constructed using UPGMA by the NTSYS-pc ver. 2.01e program based on similarity coefficient, which ranging from 0.40-0.91, and resulting in three major groups. This research could be used as a guideline for conservation and breeding in the future. Keywords: Nymphaea; start codon targeted (SCoT); dendrogram; genetic relationship; identification